Regulating Exceptions for Research and Exploratory Fishing in Southern Ocean Marine Protected Areas: A Comparative Analysis on Balancing Conservation and Commercial Use. (28th March 2022) - Liu, Nengye; Proelss, Alexander; Schatz, Valentin
Abstract: This article examines the concepts of "research fishing" and "directed fishing" under the Ross Sea region Marine Protected Area (RSrMPA) with specific regard to MPAs as a conservation tool, drawing comparisons with related concepts contained in two other agreements, namely, the 1946 International Convention for the Regulation of Whaling (ICRW) and the 2018 Agreement to Prevent Unregulated High Seas Fisheries in the Central Arctic Ocean (CAOF Agreement). It first reviews the negotiation processes of the RSrMPA, focusing on debates between so called "fishing states" and "conservation states, " as well as the political compromise that led to the establishment of the RSrMPA. Second, it takes a detailed look at the regulation of "research fishing" and "directed fishing, " which may be conducted in the RSrMPA and the three zones into which it is divided. Third, it analyzes how "scientific research activities" and "exploratory fishing" are regulated in the CAOF Agreement. Thereafter, this article examines the role of the concept of whaling "for purposes of scientific research" under the ICRW. It concludes with an assessment of differences and similarities between the analyzed regulatory instruments, which identifies recommended lessons for the design of Conservation and Management Measures establishing MPAs that both reflect the precautionary approach and strike a balance between conservation and utilization.